2019
DOI: 10.1016/j.jpain.2018.10.003
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacological Modulation of Endogenous Opioid Activity to Attenuate Neuropathic Pain in Rats

Abstract: We previously showed that spinal mGluR 1 signaling suppresses or facilitates (depending on stage of estrous cycle) analgesic responsiveness to intrathecal endomorphin 2 (EM2), a highly muopioid receptor (MOR)-selective endogenous opioid. Spinal EM2 antinociception is suppressed during diestrus by mGluR 1 when it is activated by membrane estrogen receptor alpha (mERα), and facilitated during proestrus when mGluR 1 is activated by glutamate. In the current study, we tested the hypothesis that in female rats subj… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 73 publications
0
4
0
Order By: Relevance
“…Additionally, in diestrus where E2 levels are low, mERα-mediated activation of mGluR1 suppressed spinal endomorphin 2 antinociception. However, in proestrus, which E2 levels are high, spinal endomorphin 2 antinociception was facilitated independently of mERα, namely, through glutamate-activated mGluR1 (Liu et al, 2019). Altogether, these findings underscore the significance of the interaction between mER and glutamate receptors in the regulation of neuronal activity and emphasize the need for further investigation to delineate their roles in physiological functions and in disease states.…”
Section: Glutamatementioning
confidence: 79%
“…Additionally, in diestrus where E2 levels are low, mERα-mediated activation of mGluR1 suppressed spinal endomorphin 2 antinociception. However, in proestrus, which E2 levels are high, spinal endomorphin 2 antinociception was facilitated independently of mERα, namely, through glutamate-activated mGluR1 (Liu et al, 2019). Altogether, these findings underscore the significance of the interaction between mER and glutamate receptors in the regulation of neuronal activity and emphasize the need for further investigation to delineate their roles in physiological functions and in disease states.…”
Section: Glutamatementioning
confidence: 79%
“…Related studies have shown that the intrathecal injection of group I mGluRs agonists produces persistent thermal hyperalgesia and mechanical allodynia, as well as observed prolonged spontaneous nociceptive behaviors, which are mainly dependent on the increased release of glutamate in the spinal cord (Lefebvre et al, 2000). In addition to their own activating effects, group I mGluRs also interact with other receptor systems involved in the modulation of pain signaling, such as opioid and TRPV1 channels, thus playing an important role in the chronicity of pain (Jin et al, 2012; Liu et al, 2019). However, compared with group I mGluRs agonists, the application of group II and group III mGluRs agonists did not produce any nociceptive effects, but had a pain‐relieving effect (Acher & Goudet, 2015; Mazzitelli et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, in diestrus, mERα-mediated activation of mGluR1 suppressed spinal endomorphin 2 antinociception. However, in proestrus, spinal endomorphin 2 antinociception was facilitated independently of mERα, namely, through glutamate-activated mGluR1 [ 128 ].…”
Section: Cognitive Improvements and Painmentioning
confidence: 99%